Macroeconomic Modelling of Xenophobia in South Africa: Foreign Owned SMES, Job Creation, and Economic -Wide Shocks if Migrant Entrepreneurs Exit - John Okey Onoh (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study models the economy-wide effects of xenophobia-induced exit of foreign-owned small and medium enterprises in South Africa using a 2025 Social Accounting Matrix and a static Computable General Equilibrium model. Grounded in Mixed Embeddedness Theory (Kloosterman et al., 1999) and Social Accounting Matrix Theory (Pyatt & Round, 1985), the research disaggregates retail and transport activities into local and foreign ownership using FinMark Trust (2022), Statistics South Africa QLFS Q4 2023, and National Treasury (2025) data. Six hypotheses test GDP, employment, fiscal, and welfare impacts of 25%, 50%, and 75% exit shocks to foreign entrepreneurial capital and unskilled labour. Simulation results show a 50% exit reduces real GDP by 4.97%, exceeding the 4.0% threshold, consistent with General Equilibrium Theory (Scarf, 1967) and Accelerator Theory (Clark, 1917). South African unskilled employment falls by 5.92%, yielding a complementarity elasticity of 0.83, which supports Factor Complementarity Theory (Griliches, 1969) and rejects Substitution Theory (Borjas, 2003). Government revenue declines 7.80%, twice the GDP fall, validating Tax Buoyancy Theory (Sobel & Holcombe, 1996), while the budget deficit rises to 6.24% of GDP, breaching Fiscal Sustainability Theory (Blanchard et al., 1990). Unemployment increases by 3.19 percentage points, aligned with Search and Matching Theory (Mortensen & Pissarides, 1994). Equivalent Variation indicates regressive welfare losses: poor households lose 8.0% of income versus 3.0% for rich households, consistent with Social Exclusion Theory (Sen, 2000). The claim that expelling foreigners enables a R1 million annualstipend is refuted under Government Budget Constraint Theory (Domar, 1944): post-shock revenue is R1.66 trillion, making required funds 36.7 times available resources, confirming Fiscal Illusion Theory (Puviani, 1903). Limitations include the static model structure and reliance on survey-based disaggregation shares, per CGE Model Validation Theory (Kehoe, 2005). The study concludes that xenophobia functions as an adverse covariate shock under Social Risk Management Theory (Holzmann & Jorgensen, 2001), destroying institutional capital and reducing resilience as defined by Resilience Theory (Martin, 2012). Policy recommendations integrate Policy Coherence Theory (Hoebink, 2004): Home Affairs should permit foreign SMEs conditional on South African job ratios; National Treasury should counter Fiscal Illusion with citizen budgets; and DTIC should include compliant foreign firms in industrial policy per Industrial Policy Theory (Rodrik, 2004). The findings contribute to Mixed Embeddedness Theory by demonstrating macroeconomic embeddedness of migrant entrepreneurs through Linkage Theory (Hirschman, 1958).